2001
DOI: 10.1038/sj.ijo.0801687
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish Obese Subjects (SOS) study—rationale and results

Abstract: OBJECTIVE: Obesity is associated with increased morbidity and mortality. Several observational epidemiological studies have indicated that weight gain and weight loss, even in the obese, is also related to an increased mortality. The Swedish Obese Subjects (SOS) study was initiated in 1987 as an attempt to elucidate this paradox. Design: Two thousand matched patient pairs will be followed for 10 y each. One pair member is surgically treated, while the other receives conventional obesity treatment. By February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
12

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 9 publications
1
81
0
12
Order By: Relevance
“…Weight loss was 28-76 kg after 2 y, [79][80][81][82][83][84][85][86][87][88][89] 17-73 kg after 3 y, [79][80][81][86][87][88][89] and 20 kg after 8 y in one study [82][83][84] based on a completers method of analysis. No study reported the proportion of subjects with Z5% weight loss, although this was probably high given the absolute weight loss with surgical therapy.…”
Section: Surgical Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Weight loss was 28-76 kg after 2 y, [79][80][81][82][83][84][85][86][87][88][89] 17-73 kg after 3 y, [79][80][81][86][87][88][89] and 20 kg after 8 y in one study [82][83][84] based on a completers method of analysis. No study reported the proportion of subjects with Z5% weight loss, although this was probably high given the absolute weight loss with surgical therapy.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Only two studies assessed this, [82][83][84]88 thereby precluding meaningful commentary. In one study that compared surgical and nonsurgical weight loss after 8 y, the risk of type 2 diabetes was 84% less with surgery (OR ¼ 0.16; 95% CI: 0.07-0.36) but there was no effect on the risk of hypertension (OR ¼ 1.01; 95% CI: 0.61-1.67).…”
Section: Surgical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In adults, RYGB results in remission and prevention of T2DM, 104,105 with normalization of fasting hyperglycemia in 64-83% of type 2 diabetic patients and 99% of those with impaired glucose tolerance. 26,36 Improvements in insulin resistance and b-cell function have been documented following surgical weight loss.…”
Section: Endocrine Changesmentioning
confidence: 99%